Cutaneous Polyarteritis Nodosa: A Case Report - Fitriend Syahputri; Dina Arwina Dalimunthe; Richard Hutapea (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cutaneous polyarteritis nodosa is a rare type of vasculitis that involves inflammation in small to medium-sized blood vessels, mainly targeting the skin. It affects people of all ages and significantly impacts both the skin and other organ systems. This case report aims to describe the clinical presentation, diagnostic approach, and therapeutic response. A 38-year-old man came with a two-week history of a red, non-itchy rash on both legs. A week before the rash appeared, patient experienced fever, sore throat, and stomach pain. His general condition was stable. Dermatological examination showed multiple palpable purpura on both legs, ranging from miliary to lenticular in size. Diascopy revealed non-blanching purpura, and dermoscopy showed a homogeneous pattern of multiple erythematous spots. Histopathology indicated a proliferation of blood vessels with enlarged endothelial cells, concluding with a diagnosis of polyarteritis nodosa. Patient was diagnosed with cutaneous polyarteritis nodosa and treated with methylprednisolone at 1 mg/kg/day, divided into three doses of 32 mg each, with tapering off every week. Clinical improvement was observed, and the skin lesions progressively resolved. This case highlights the importance of early recognition and corticosteroid therapy in the successful management of mild cutaneous polyarteritis nodosa. Keywords: corticosteroid, cutaneous polyarteritis nodosa, vasculitis